PS2-38: Cancer Research Network: Cancer Incidence, Prevalence, and Health Plan Enrollment - Chubak, Jessica (Clin Med Res, 2014)
BACKGROUND/AIMS: Nested within the HMO Research Network (HMORN), the Cancer Research Network (CRN) is a collaboration among the National Cancer Institute, 9 funded HMORN sites, 6 affiliate sites, and scientific collaborators from multiple institutions. Now in its fourth cycle, the CRN has been funded continuously since 1999. CRN’s goals are to build data infrastructure, expertise, and collaborations to promote successful cancer research involving integrated healthcare delivery systems. Understanding characteristics of incident and prevalent cancer cases in the CRN is essential for investigators to evaluate the feasibility of CRN research projects. METHODS: Characteristics of health plan enrollees and prevalent (i.e., history of) and incident cancers were collected across the 9 funded CRN sites. Data were obtained from the CRN Cancer Counter – a tool to aggregate patient counts across sites from centralized summary data–as well as a centrally-developed SAS® program run against each site’s Virtual Data Warehouse. Descriptive analyses focused on distributions of malignant cancer incidence and prevalence by age and anatomic site as well as by length of enrollment before and after diagnosis. RESULTS: As of mid-2013, more than 9 million persons were enrolled in CRN site health plans. Of those enrollees, more than half a million were diagnosed with cancer during or before each site’s last available year of cancer incidence data (2008–2011, varied by site). Prostate, breast, non-melanoma skin, and colon cancers had the highest prevalence and incidence. Overall, 22% of survivors were diagnosed prior to 1998. Examination of enrollees at one CRN site with a diagnosis of cancer in 2011 found that nearly half had been enrolled in the health plan for at least 15 years prior to diagnosis. Enrollment for cancer patients will be examined at additional CRN sites. CONCLUSIONS: The CRN is an excellent setting for prospective and retrospective studies of cancer etiology, screening, treatment and outcomes. Long periods of enrollment prior to cancer diagnosis facilitate retrospective studies of cancer etiology. Large numbers of cancer survivors with low disenrollment rates facilitate prospective observational studies and trials focused on cancer outcomes.